Radiologic and Clinical Outcome of the Operated and Adjacent Segments Following Prodisc-C Cervical Arthroplasty After a Minimum 24-month Follow-up: A Single Surgeon-center Experience. Issue 3 (August 2016) - Sirikci, Murat; Karaca, Sinan; Enercan, Meric; Sarier, Mercan; Erdem, Mehmet N.; Alanay, Ahmet; Hamzaoǧlu, Azmi
Abstract : Study Design: This was a retrospective study. Objective: The purpose of this retrospective study was to determine the radiologic outcome at the index and adjacent levels and clinical outcome of cervical total disk arthroplasty (TDA) using Prodisc-C after a minimum 24 months follow-up at a single center. Methods: Eighty-six levels of 59 (28 female, 31 male) cases with minimum 2 years follow-up were included in this study. Radiologic parameters including disk level height at the operated and adjacent levels, global cervical lordosis, segmental lordosis, range of motion, subsidence, facet arthrosis, adjacent segment degeneration (ASD), and heterotopic ossification were analyzed. All surgeries were performed by a single surgeon. Results: Average age was 39.5 (range, 27 to 56) years and average follow-up was 33.6 (range, 24 to 81) months. Operated levels were C3-4 (%4.6), C4-5 (%16.3), C5-6 (%48.8), C6-7 (%26.8), and C7-T1 (%3.5). All patients had clinical improvement. NDI was improved from 46 to 9. There was a significant improvement in segmental kyphosis, global lordosis, and disk height at the operated level with no significant change at the final follow-up. There was no radiographic facet joint arthrosis at the index and adjacent levels, 4 (%6.7) patients had radiographic signs of ASD at the cranial adjacent level, whereas 5 (%8.4) patients had ASD at the caudal adjacent level. Heterotopic ossification (HO) was observed in 4 patients (%6.7) with a complete fusion in 1 patient. Conclusions: This study demonstrates a satisfactory radiographic and clinical outcome after prodisc-C TDA with a minimum 24-month follow-up.